Situational Analysis of Human Resource and Material Management Skills of Middle Level Health Care Managers at Primary Health Centres of Valsad, Gujarat: Identifying Barriers and Suggesting an Action Plan - Neha A Patel; Bhavesh R Bariya; Rachana G Kapadia (Medsci Publications, 2022)
Background: Management of Human resources in health has been a major challenge. Availability of manpower and material are the key ingredients required for efficient and effective delivery of health services. Removing the barriers related to it can help to improve functioning of PHCs Objectives:  1. To analyze Human resource and Material management skills at PHCs by middle level healthcare managers. 2. To understand the constraints for effective management at PHCs.   Materials and Methods: A cross sectional study was conducted amongst 38 Medical officers who were selected by simple random sampling method. Data collection was done using a semi structured and scale-based questionnaire adopted from NIHFW, India. Results: Almost half medical officers had experience of less than one year. Only 10.5% PHC/CHCs have full staff. 47.3% health facilities were lacking AYUSH MOs. 63.2% health facilities faced stock out of at least one item in last six months; Lack of manpower (34.8%) and overburden of work (27.9%) are major barriers. Conclusions: 90% PHCs have one or more posts vacant. Material management need to be improved for better provision of services. Major barriers are lack of Manpower, Infrastructure and Multitasking.